Solid state electronic devices - Streetman, Ben G. (New Jersey : Prentice-Hall, 1995)
Aiming to provide students with a sound understanding of existing devices in order to develop the basic tools with which they can later learn about applications and the latest devices, this study incorporates the basics of semiconductor materials and conduction processes in solids. It also introduces and relates the most commonly used semiconductor terms and concepts to a broad range of devices. In addition, the work presents the study of solid state devices including both silicon and compound semiconductors so that undergraduate students may appreciate the continuing growth in importance of exciting optoelectronic and high-speed device applications.
Keywords: SEMICONDUCTORS